Correlation and path coefficient analysis of yield and yield components of some Ethiopian faba bean (Vicia faba L.) accessions - Andualem Muche HIYWOTU; Alemu ABATE; Fisseha WOREDE (Acta Agriculturae Slovenica, 2023)
The knowledge of correlation and path coefficient analysis allow crop breeders to practice indirect selection to improve traits like grain yield which are complex in nature. The objectives of the present study were to measure association among yield and yield related traits and to identify important traits for indirect selection to improve faba bean grain yield. Eighty-one faba bean accessions were evaluated following 9 × 9 simple lattice design at one of the Bahir Dar University research sites at Mecha district in 2019 rainy cropping season. The result of correlation analysis revealed that grain yield had highly significant (p < 0.01) and positive phenotypic and genotypic correlations with plant height, pod length, number of pods per plant, number of branches per plant, biomass yield, 100-seed mass and harvest index indicating the possibility of simultaneous improvement of grain yield with these traits through selection. Path coefficient analysis demonstrated that higher positive direct effects were exerted by biomass yield and harvest index on grain yield both at phenotypic and genotypic levels, as a result, these traits could be used as indirect selection criteria to improve faba bean grain yield.